Zhuangzi : Text and Context. - Kohn, Livia (Three Pines Press, 2016)
Zhuangzi: Text and Context is a comprehensive discussion of the ancient Daoist work Zhuangzi in 24 chapters, providing a chronologically-based outline of the context of the work, from the compilation of the text to its reading in 21st century ecology, plus a systematic discussion and interpretation of its central concepts from perfect happiness to playful uselessness. The book integrates a vast spectrum of original and secondary sources, examines the history and ideas in a wide context, both within China and cross-culturally, and relates many of Zhuangzi's key notions and practices to modern s.